Incidence of Liver and Non-liver Cancers After Hepatitis C Virus Eradication: A Population-Based Cohort Study - José Ríos; Víctor Sapena; Zoe Mariño; Jordi Bruix; Xavier Forns; Rosa Morros; María Reig; Ferran Torres; Caridad Pontes (Adis, Springer Healthcare, 2024)
Abstract Background and Objectives Direct-acting antivirals (DAAs) offer a high rate of hepatitis C virus (HCV) eradication. However, concerns on the risk of cancer after HCV eradication remain. Our study aimed at quantifying the incidence of cancer in patients treated with anti-HCV therapies in Catalonia (Spain) and their matched controls. Methods This was a population-based study using real-world data from the public healthcare system of Catalonia between 2012 and 2016. Propensity score matching was performed in patients with HCV infection treated with interferon-based therapy (IFN), sequential IFN and DAA (IFN+DAA), and DAA only (DAA) with concurrent controls. We estimated the annual incidence of overall cancer, hepatocellular carcinoma, and non-liver cancer of HCV-treated patients and their corresponding rate ratios. Results The study included 11,656 HCV-treated patients and 49,545 controls. We found statistically significant increases in the rate of overall cancer for IFN+DAA-treated (rate ratio [RR] 1.77, 95% confidence interval [CI] 1.27-2.46) and DAA-treated patients (RR 1.90, 95% CI 1.66-2.19) and in the rate of HCC for IFN-treated (RR 1.50, 95% CI 1.02-2.22), IFN+DAA-treated (RR 3.89, 95% CI 2.26-6.69), and DAA-treated patients (RR 6.45, 95% CI 4.90-8.49) compared with their corresponding controls. Moreover, DAA-treated patients with cirrhosis showed an increased rate of overall cancer versus those without cirrhosis (RR 1.92, 95% CI 1.51-2.44). Conclusions Results showed that overall cancer and hepatocellular carcinoma incidence in Catalonia was significantly higher among HCV-treated patients compared with matched non-HCV-infected controls, and risks were higher in patients with cirrhosis. An increased awareness of the potential occurrence of uncommon malignant events and monitoring after HCV eradication therapy may benefit patients.